Preferences for methadone clinics among drug users in Vietnam : a comparison between public and private models - Le, Tuan Anh (2021)
Background: Methadone maintenance treatment (MMT) has been proven to be effective in treating opioid dependence. In Vietnam, MMT services are provided primarily by public clinics, with only one private MMT clinic established in recent years. Assessing the preferences of patients for different MMT models is important in evaluating the feasibility of these models. This study measured the preferences of drug users enrolling in public and private MMT clinics in Vietnam and examines the related factors of these preferences. Methods: A cross-sectional study was performed on 395 participants at 3 methadone clinics in Nam Dinh. Data about the preferences for MMT models and sociodemographic characteristics of participants were collected.Exploratory factor analysis was employed to explore the construct validity of the questionnaire. The chi-square test and Mann-Whitney test were used for analyzing demographic characteristics and preferences of participants.Multivariate logistic regression identified factors associated with participants’ preferences. Results: Half the participants received MMT treatment in a private facility (49.4%). Two preference dimensions were defined as“Availability and convenience of service”and“Competencies of clinic and health professionals”. Self-employed patients were more likely to consider these two dimensions when choosing MMT models. Only 9.9% of participants chose“Privacy”as one of the evaluation criteria for an MMT facility. Compared to public clinics, astatistically higher percentage of patients in the private clinic chose the attitudes of health workers as the reason for using MMT service (34.7% and 7.6% respectively). Mean score of satisfaction towards MMT services was 8.6 (SD =1.0), and this score was statistically higher in a public facility, compared to the private facility (8.7 and 8.4respectively). Conclusions: The study highlighted patterns of patient preferences towards MMT clinics. Compared to the public MMT model, the private MMT model may need to enhance their services to improve patient satisfaction.